A Review of BFT Consensus Algorithms and Their Application in Modern Blockchain Protocols - Brandon Vrooman (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
This article examines modern Byzantine fault-tolerant (BFT) consensus algorithms as key mechanisms for ensuring the reliability and robustness of blockchain protocols. The study identifies the structural properties of classical, linear, asynchronous, and hybrid consensus models under high loads and network uncertainty. Using comparative and structural-functional analyses, the research isolates architectural features defining resilience, validator organization, and finality. Furthermore, an applied framework is developed to select consensus algorithms based on phase structures, communication models, and fault types. This framework accounts for architectural constraints and operational conditions, determining protocol applicability across diverse blockchain platforms. Ultimately, it provides practical guidelines for designing scalable, fault-tolerant distributed systems